2022
DOI: 10.1016/j.eats.2021.08.037
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Double-Bundle Anterior Cruciate Ligament Reconstruction by the Three-Inside Technique With Two Suspension Buttons and One Interference Screw

Abstract: In comparison with the single-bundle technique, double-bundle anterior cruciate ligament (ACL) reconstruction has proven its superiority regarding biomechanical studies and clinical outcomes in both rotational knee stability and anterior translation function. However, the complexity and risk of complications remain a great concern for the orthopaedic surgeon performing double-bundle ACL reconstruction. We present a simplified double-bundle ACL reconstruction by the 3-inside technique with 2 suspension buttons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(14 reference statements)
0
1
0
Order By: Relevance
“… 17 Recent published surgical techniques for the db procedure including ours performed a triple- or quadruple-fold for the AM bundle to achieve a minimum diameter of 8 mm. 18 , 19 Furthermore, the mean age for their study was 22 years of age and numerous studies have shown adolescents and teenagers to be the age groups with greatest incidence and risk of ACL tear and graft failure after reconstruction. 20 , 21 , 22 , 23 , 24 , 25 This increase risk could be due to hormonal changes as the ACL is now known to host sex hormone receptors.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Recent published surgical techniques for the db procedure including ours performed a triple- or quadruple-fold for the AM bundle to achieve a minimum diameter of 8 mm. 18 , 19 Furthermore, the mean age for their study was 22 years of age and numerous studies have shown adolescents and teenagers to be the age groups with greatest incidence and risk of ACL tear and graft failure after reconstruction. 20 , 21 , 22 , 23 , 24 , 25 This increase risk could be due to hormonal changes as the ACL is now known to host sex hormone receptors.…”
Section: Discussionmentioning
confidence: 99%